Flexible Photocatalytic Electrode Using Graphene, Non‐noble Metal, and Organic Semiconductors for Hydrogen Evolution Reaction. Issue 8 (28th May 2021) - Kondo, Kohei; Watanabe, Yusuke; Kuno, Junya; Ishii, Yosuke; Kawasaki, Shinji; Kato, Masashi; Kalita, Golap; Hattori, Yoshiyuki; Mashkov, Oleksandr; Sytnyk, Mykhailo; Heiss, Wolfgang
Abstract : Two kinds of visible light‐responsible organic semiconductors (epindolidione [EPI] and fluorinated EPI [2F‐EPI]) are synthesized. The solar hydrogen evolution photocatalytic electrode properties of the organic semiconductors are investigated and the heterostructure effect caused by manipulating the order of the deposition of 2F‐EPI and EPI is found, which increased the photoresponse current by reducing the carrier recombination of photoexcited electrons and holes. In addition, it is found that the deposition of Ni metal on the organic semiconductors further enhanced the photoresponse current and increased the durability of the organic semiconductor photocatalyst. Finally, a flexible photocatalytic electrode using graphene, organic semiconductors, and non‐noble metal cocatalyst for solar hydrogen generation is prepared. A transparent flexible electric conductive film is prepared by transfer of a graphene sheet on the polymer film. The graphene electrode is coated by two kinds of organic semiconductors layer by layer to reduce recombination of photoexcited electrons and holes. Ni metal particles are deposited on the surface of the organic semiconductor layer as a cocatalyst to improve the photocatalytic property and durability of organic semiconductors. A clear photoresponse current (about 4 μA cm −2 ) of the flexible photocatalytic electrode under the simulated solar light (AM 1.5 G, 100 mW cm −2 ) is observed. Abstract : A flexible photocatalytic hydrogen evolution electrode is developed.